The effect of Swiss ball exercises on developing explosive strength in the arms and legs and some offensive basketball skills (under 18 years) - محمد, م. ديندار فيضي محمد (Sulaimani Journal for Humanities, 2025)
The Swiss ball is a small-sized rubber ball, available in several colors, filled with the appropriate pressure of air, with a diameter ranging from 55 cm to 95 cm, to suit the sizes of everyone who trains on it. There is no demand for using exercises using Swiss balls because they require tools different from other training methods, and from here the problem of the study arose for the researcher, which can be summarized by the following question: Is there an effect of exercises using Swiss balls in developing some of the physical abilities and offensive skills of basketball players? The current research aims to reveal the significance of the statistical differences in the explosive power of the arms and legs between the pre- and post-tests for the players of the experimental group that used Swiss ball exercises and for the players of the control group that used the traditional exercises. To reveal the significance of the statistical differences in a number of offensive basketball skills between the pre- and post-tests. For the players of the experimental group that used Swiss ball exercises and for the players of the control group that used traditional exercises, to identify the significance of statistical differences in the explosive power of the arms and legs and in a number of offensive skills in basketball between the experimental group and the control group in the post-test. Research method: The researcher used the experimental method. To suit the nature of the research, the research community and its sample: The research community included the Dohuk Sports Club basketball players for the under-18 age group, who numbered (16) players representing the youth category. As for the research sample, they were chosen intentionally, with the final number reaching (12) players after the researcher excluded a number of the sample members for conducting reconnaissance and injury experiments, and their number was (4) players. The research sample was divided by lottery into two groups (6) players for the experimental group and (6) As a player for the control group, the researcher used the statistical package (spss) to find the following statistical means: the arithmetic mean, the standard deviation, the percentage, the coefficient of skewness, the coefficient of variation, and the t-test for related samples and for independent samples. The researcher concluded that exercises using the Swiss ball bring about a development in the explosive power of the arms. And the legs. Exercises using the Swiss ball bring about development in a number of offensive skills in basketball (thoracic and long handling, diving, and scoring from the jump). Exercises using the Swiss ball bring about development in the explosive power of the arms and legs and a number of offensive basketball skills (chest and long handling). And diving and scoring from jumping) better than using regular traditional exercises.